Transition Metal Disulfides as Noble-Metal-Alternative Co-Catalysts for Solar Hydrogen Production - Chang, Kun; Hai, Xiao; Ye, Jinhua (Advanced energy materials, 2016)
The production of hydrogen fuels by using sunlight is an attractive and sustainable solution to the global energy and environmental problems. Platinum (Pt) is known as the most efficient co‐catalyst in hydrogen evolution reaction (HER). However, due to its high‐cost and limited‐reserves, it is highly demanded to explore alternative non‐precious metal co‐catalysts with low‐cost and high efficiency. Transition metal disulfides (TMDs) including molybdenum disulfide and tungsten disulfide have been regarded as promising candidates to replace Pt for HER in recent years. Their unique structural and electronic properties allow them to have many opportunities to be designed as highly efficient co‐catalysts over various photo harvesting semiconductors. Recent progress in TMDs as photo‐cocatalysts in solar hydrogen production field is summarized, focusing on the effect of structural matchability with photoharvesters, band edges tunability, and phase transformation on the improvement of hydrogen production activities. Moreover, recent research efforts toward the TMDs as more energy‐efficient and economical co‐catalysts for HER are highlighted. Finally, this review concludes by critically summarizing both findings and current perspectives, and highlighting crucial issues that should be addressed in future research activities. Recent progress in the use of transition metal disulfides as noble‐metal‐alternative photo‐cocatalysts in the solar hydrogen production field is reviewed, focusing on the effect of structural matchability with photoharvesters, band edges tunability, and phase transformation on the improvement of hydrogen production activities. Moreover, both findings and current perspectives are critically summarized, highlighting crucial issues that should be addressed in future research activities.